2017
DOI: 10.4317/jced.53790
|View full text |Cite
|
Sign up to set email alerts
|

Remineralizing effect of a zinc-hydroxyapatite toothpaste on enamel erosion caused by soft drinks: Ultrastructural analysis

Abstract: BackgroundThe aim of the present in vitro study was to evaluate the protective effects of a zinc-hydroxyapatite toothpaste on repairing enamel erosion produced by a soft drink (Coca-Cola) compared to toothpastes with and without fluoride using Scanning Electron Microscopy (SEM).Material and MethodsFifty specimens were assigned to 5 groups of 10 specimens each. (Group 1: no erosive challenge, no toothpaste treatment, group 2: erosive challenge, no toothpaste treatment, 3: erosive challenge, toothpaste without f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
3
17
0
2
Order By: Relevance
“…It is well documented in literature that tooth erosion attributed to high consumption of citric acid containing soft drinks is increasingly seen as a public health concern, thus contributing to DH. 18 The potential strategy for management of DH is to effectively occlude the dentine tubules. The purpose of this study was to synthesized and evaluate the effectiveness of a ball-milled synthesized EB@TiO 2 to occlude open dentine tubules.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented in literature that tooth erosion attributed to high consumption of citric acid containing soft drinks is increasingly seen as a public health concern, thus contributing to DH. 18 The potential strategy for management of DH is to effectively occlude the dentine tubules. The purpose of this study was to synthesized and evaluate the effectiveness of a ball-milled synthesized EB@TiO 2 to occlude open dentine tubules.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that bovine and enamel models be used when examining the effectiveness of commercial toothpaste against acidic attacks. 16,17 Also considered as the sole test model was the dissolution of hydroxyapatite (HA). 18,19 It is generally well known that tooth enamel consists mostly of calcium hydroxyapatite with a molecular formula of Ca 10 (PO 4 ) 6 (OH) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the zinc level was set at 10 mmol/L based on the recommended intake (11 mg/day) and maximum permissible intake (40 mg/day) of zinc for humans. Creeth et al [30] and Colombo et al [31] also reported in their in vitro study using dentifrices and bovine enamel specimens that zinc increased demineralization resistance. The discrepancy between the present study and these previous reports could be due to differences in experimental methods.…”
Section: Discussionmentioning
confidence: 92%